Viscoelastic-adhesive modeling of hybrid adhesively bonded double-lap joints: analytical and numerical studies - Cay, Mustafa; Ozer, Halil (TAYLOR & FRANCIS LTD, 2025)
There are a limited number of studies examining the viscoelastic and viscoplastic behavior of adhesive joints. If there is more than one adhesive in the overlap region, the problem becomes more complex and viscoelastic modeling of the overlap region becomes difficult. There is no study in the literature that covers such a bonding (overlap) scheme and examines the viscoelastic behavior of the double lap joint (DLJ). In this study, the effect of viscoelasticity of polymeric adhesives on shear stress and strain distributions in the hybrid-adhesive layer of a DLJ is studied. Maxwell-Wiechert (MW) viscoelastic material model is used to define the viscoelastic behavior of the adhesives. Analytical and finite element (FE) results are compared for both mono- and hybrid-adhesive joints under the step load. Good matches are observed between the analytical and numerical results. Four different hybrid-adhesive joints with different combinations of the adherend thicknesses are investigated by considering only the analytical method. In order to investigate the effect of the loading type on the viscoelastic behavior, step and ramp loads were applied to the joint separately. It is observed that applying the ramp load to the hybrid-adhesive joints affects the shear stresses occurred at the ends of the overlap more than the mono-adhesive joints.
Keywords: Hybrid-adhesive; mixed-adhesive; bi-adhesive; double-lap joints; prony series; viscoelasticity; BEHAVIOR; Engineering; Materials Science; Mechanics